You are on page 1of 7

# Mathematics Primer Exercises

## 1 Calculus Problem Sheet

1. Consider two functions f (x) = 9x + 2 and g (x) = x9 2
9: Show that they
are inverse functions of one another.
This simply requires showing f (g (x)) = g (f (x)) = x

x 2
f (g (x)) = 9 +2=x 2+2=x
9 9
9x + 2 2 2 2
g (f (x)) = =x+ =x
9 9 9 9

## 2. Obtain the inverse of the function f (x) = x1=3 + 2:

y = x1=3 + 2 ! x1=3 = y 2
3
x = (y 2) = g (y)
) 1 3
f (x) = g (x) = (x 2)

## 3. Calculate the following limits:

x2 4 (x + 2) (x 2)
lim = lim = lim (x + 2) ! 4
x!2 x 2 x!2 x 2 x!2

x2 x x (x 1) x 1
lim = lim = lim !
x!1 2x2 + 5x 7 x!1 (2x + 7) (x 1) x!1 (2x + 7) 9
p p p
x+5 x+5 x+5
lim = lim p p = lim p p !1
x! 25 x 25 x! 25 ( x 5) ( x + 5) x! 25 ( x 5) ( x + 5)
3
(x + h) x3
lim : see primer lecture notes
h!0 h
3
h3 + 8 (h + 2) 6h (h + 2) 2
lim = lim = lim (h + 2) 6h ! 12
h! 2 h+2 h! 2 h+2 h! 2

(1=t) 1 (1 t) =t (t 1) =t 1
lim = lim = lim lim ! 1
t!1 t 1 t!1 t 1 t!1 t 1 t!1 t
p
lim
p x2 + 3 (x 4) = lim
p x2 + 3 lim
p (x 4) ! 5 2 4
x! 2 x! 2 x! 2

1
4. Using the de…nition of the derivative, show that for

y 2x + 1; y 0 = 2
=
[2 (x + h) + 1] (2x + 1) 2x + 2h + 1 2x 1 2h
y 0 = lim = lim = lim = lim 2 = 2
h!0 h h!0 h h!0 h h!0
1 0 1
f (x) = ; f (x) = 2
x 2 (x 2)
1 1
x 2+h x 2 1 (x 2) (x 2 + h) 1 h
f 0 (x) = lim = lim = lim
h!0 h h!0 h (x 2 + h) (x 2) h!0 h (x 2 + h) (x 2)
1 1
= lim = 2
h!0 (x 2 + h) (x 2) (x 2)

## g (x) = jx 5j ; no derivative exists at x = 5

0 g (x + h) g (x) 0 g (5 + h) g (5) j5 + h 5j j0j
g+ (x) = lim ! g+ (5) = lim = lim
h!0+ h h!0+ h h!0+ h
jhj h
= lim = lim =1
h!0+ h h!0+ h
g (x + h) g (x) g (5 + h) g (5) j5 + h 5j j0j
g 0 (x) = lim ! g 0 (5) = lim = lim
h!0 h h!0 h h!0 h
jhj h
= lim = lim = 1
h!0 h h!0+ h
0
g+ (x) = g 0 (x) ) the derivative does not exist at x = 5:
dy
5. Di¤erentiate the following functions y; to obtain :
dx
We know the Chain Rule:
dy df du
y = f (u) where u = F (x) then =
dx du dx

5
y = x2 4x + 2
dy 4
= 5u4 : (2x 4) = 5 x2 4x + 2 (2x 4)
dx

1 3
y = 3 = 4x2 + 6x 7
(4x2 + 6x 7)
dy 4
= 6 4x2 + 6x 7 (4x + 3)
dx
y 4 + 3y 4x3 = 5x + 1
implicit di¤erentiation:
dy 5 + 12x2
=
dx 4y 3 + 3

2
q
3 2 2=3 2
y = ln (2x + 5) = ln (2x + 5) = ln (2x + 5))
3
dy 4
=
dx 3 (2x + 5)
dy
y = cos (4 3x) : = 3 sin (4 3x)
dx
Now use the product rule:
dy
y = x2 exp(x) : = xex (2 + x)
dx
Next problem requires the quotient role
3x2 x + 2
y =
4x2 + 5
4x2 + 5 (6x 1) 8x 3x2 x+2
y0 = 2
(4x2 + 5)
6. Calculate the following
Z Z
p
x x2 4x + 2 dx = x5=2 4x3=2 + 2x1=2 dx
2 7=2 8 5=2 4 3=2
= x x + x +C
7 5 3
Z 1 p p
3 x+1 x 2 dx =
4
Z 1 1
3 2 10 3=2 41
3x 5x1=2 2 dx = x x 2x =
4 2 3 4 6

Z 2
(2s 7)
ds
1 s3
Z 2 2 2
2 7 2 7 29
= + 3 ds = + =
1 s2 2s s 1 2s2 1 8

Z 2
x2 1
dx =
3 (x 1)
Z 2 2
x2 7
(x + 1) dx = +x =
3 2 3 2

Z 5 Z 3=2 Z 5
j2x 3j dx = (3 2x) dx + (2x 3) dx
1 1 3=2
3
5 37
= 3x x2 2
1
+ x2 3x 3 =
2 2

3
Z
5x 12 5x 12 3 2
dx : +
x (x 4) x (x 4) x (x 4)
Z Z
3 2
= + = 3 ln x + 2 ln (x 4) + C
x (x 4)
2
= ln x3 (x 4) + C

Z
3
3 x4 x3 dx

## let z = 3 x4 so that dz = 4x3 dx and the integral becomes

Z
1 1 4
z 3 dz = 3 x4 + c
4 16
Z
x2 + x
4 dx
(4 3x2 2x3 )
put z = 4 3x2 2x3 so that dz = 6 x2 + x dx to give
Z
1 1 1
4
dz = 3 +c
6 z 18 (4 3x2 2x3 )
Z p 4
( u + 3)
p du
u
p 1
let z = u+3= so that dz = p
2 u
du and we have
Z p 5
z5 2 ( u + 3)
2 z 4 dz = 2 +c= +c
5 5
Z 3
1 1
1+ du
u u2
1 1
let z = 1 + u so that dz = u2 du and
Z 2
3 1 1
z dz = 1+
2 u
Z
2
xex dx

## let z = x2 so that dz = 2xdx; so

Z
1 1 1 2
ez dz = ez + c = ex + c
2 2 2

4
Z
(sin x) ecos x dx

## let z = cos x so that dz = (sin x) dx

Z
ez dz = ez + c = ecos x + c

## 8. If f (x; y) = (x y) sin (3x + 2y) ; determine fx ; f y ; fxx ; fyy ; fxy ; fyx :

Now evaluate these expressions at (0; =3) :
fy = 2 (x y) cos (3x + 2y) sin (3x + 2y)

## fx = sin (3x + 2y) + 3 (x y) cos (3x + 2y)

fxx = 6 cos (3x + 2y) 9 (x y) sin (3x + 2y)

## fyy = 4 cos (3x + 2y) 4 (x y) sin (3x + 2y)

fxy = fyx = cos (3x + 2y) 6 (x y) sin (3x + 2y)
Now evaluate these expressions
p at x = 0; y = =3.
We use sin (2 =3) = 3=2; cos (2 =3) = 1=2
p p
3 3
fx 0; = + ; fy 0; =
3 2 2p 3 3 2
3 2
fxx 0; = 3+3 ; fyy 0; =2+ p
3 2 3 3
1 p
fxy 0; = + 3
3 2
2 2
9. Show that z = ln z = ln (x a) + (y b) satis…es

@2z @2z
+ =0
@x2 @y 2
2 2
except at (a; b) : Write z = ln u; u = (x a) + (y b)
@z 2 (x a) @z 2 (y a)
= ; =
@x u @y u
2 2
@2z 2u 4 (x a) @2z 2u 4 (y b)
= ; =
@x2 u2 @y 2 u2

2 2
@2z @2z 2u 4 (x a) + 2u 4 (y b)
2
+ 2 =
@x @y u2
2 2 2 2
4 (x a) + (y b) 4 (x a) 4 (y b)
= =0
u2

5
10. Obtain Taylor series expansions for the following functions about the given
point x0 : If no point is given, then expand about the point 0 (in which
case you can use standard Taylor series expansions)
x3 x5 n x2n+1
f (x) = x2 sin x = x2 x + ::::::::::::: + ( 1)
3! 5! (2n + 1)!
1
X n x2n+3
= ( 1)
n=0
(2n + 1)!

f (x)
cos x; x0 = =3 =
X1
f (n) (x0 ) n
f (x) = (x x0 )
n=0
n!
p p
f ( =3) = 1=2; f 0 ( =3) = 3=2; f 00 ( =3) = 1=2; f 000 ( =3) = 3=2; f (4) ( =3) = 1=2
The Taylor series expansion about x = =3 is thus f (x) = cos x =
p p (n)
2 3 4 n
1
2 2
3
x 3
1
4 x 3 + 123 x 3
1
+ 48 x 3 +:::::+ f ( =3)
n! x 3 +::

## f (x) = exp x; x0 = 3 : put u = x + 3 and expand eu about u = 0

X1 n X1 n
u (x + 3)
eu = ! ex+3 =
n=0
n! n=0
n!
1
X n
(x + 3) 2 3
ex = e 3
=e 3
1 + (x + 3) + 1
2! (x + 3) + 1
3! (x + 3) + ::::::::
n=0
n!

1 1
f (x) = = (1 4x)
1 4x
1
X
= 1 + 4x + 16x2 + 64x2 + :::::: + 4n xn = 4n xn
n=0

## this is a convergent series with jxj < 1=4:

3 1 1 2
f (x) = = 3 (2x + 5) =3 5 1+ x
2x + 5 5
2 4 2 3 n 2 n
1+ x = 1 2
5x + 25 x
8
125 x + ::: + ( 1) 5 xn
5
1
X n 2 n
f (x) = 3
5 ( 1) 5 xn : 2
5x < 1 () jxj < 5=2
n=0

1
X 1
X 1
X
x2 + 1 1
f (x) = = x2 + 1 (1 x) = x2 + 1 xn = xn+2 xn
x 1 n=0 n=0 n=0
1
X
= 1 x 2 xn
n=2

6
11. If U (x; y; z) = 2x2 yz + xz 2 ; where x = 2 sin t; y = t2 t + 1; z =
3 exp ( t) ;
dU
…nd at t = 0:
dt

dx dy dz
= 2 cos t; = 2t 1; = 3e t
dt dt dt
@U @U @U
= 4x + z 2 ; = z; = y + 2xz
@x @y @z

dU dx @U dy @U dz @U
= + + = (2 cos t) 4x + z 2 + (2t 1) ( z) + 3e t ( y + 2xz)
dt dt @x dt @y dt @z
= (2 cos t) 4 sin t + 9e 2t + (2t 1) 3e t + 3e t t2 + t 1 + 12e t sin t
dU
= (2) (9) + ( 1) ( 3) + ( 3) ( 1) = 24
dt t=0

## 12. Given w = f (x; y) ; x = r cos ; y = r sin ; show that

2 2 2 2
@w 1 @w @w @w
+ = +
@r r2 @ @x @y

xr = cos ; x = r cos
yr = sin ; y = r cos
Now use chain rule II
@w @w @x @w @y @w @w
= + = cos + sin
@r @x @r @y @r @x @y
2 2 2
@w @w @w @w @w
= cos2 + sin2 + sin 2 (1)
@r @x @y @x @y
Similarly
@w @w @x @w @y @w @w
= + = r sin + r cos
@ @x @ @y @ @x @y
2 2 2
1 @w @w @w @w @w
= sin2 + cos2 sin 2 (2)
r2 @ @x @y @x @y
@w 2 1 @w 2
(1) + (2) gives @r + r2 @ =
2 2
@w @w
sin2 + cos2 + sin2 + cos2
@x @y
2 2
@w @w
+
@x @y